PERFORMANCE ANALYSIS OF INVERTER-FED SINGLE-PHASE INDUCTION MOTOR (Journal of Engineering, 2009)
This study investigates the effects of the presences of harmonics in the exciting voltagewhen using a dc/ac inverter on the performance of a single-phase induction motor, theinvestigation includes theoretical and experimental parts and together with performancecomparison of the motor with the nominal sinusoidal input voltage. The computedperformance of the motor depend on the theoretical equivalent circuits which are modifiedto take into account the existence of harmonics in the inverter output to compute theperformance at each harmonic order. It conclude from the analysis that the pulsating torqueis inherent in single-phase induction motor even when supplied from a sinusoidal voltagesource. Particular attention has been devoted to the pulsating torque when the motor issupplied from an inverter and the most important pulsations have been identified. Thecomparisons of simulation and measured results show good correlation between them inaddition that it highlight and identify the cumulative effects of harmonics on the motorperformance.